2020
DOI: 10.3389/fcell.2020.577259
|View full text |Cite
|
Sign up to set email alerts
|

New Amphiphilic Squalene Derivative Improves Metabolism of Adipocytes Differentiated From Diabetic Adipose-Derived Stem Cells and Prevents Excessive Lipogenesis

Abstract: Squalene (Sq) is a natural compound, found in various plant oils, algae, and larger quantity in deep-sea shark liver. It is also known as an intermediate of cholesterol synthesis in plants and animals including humans. Although evidences demonstrated its antioxidant, anticancer, hypolipidemic, and hepatoprotective and cardioprotective effects, its biological effects in cellular function might have been underestimated because of the water-insoluble property. To overcome this hydrophobicity, we synthesized new a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Studies have reported the anticancer property of squalene [26] . Ganbold et al [27] reported a new amphiphilic squalene derivative improves metabolism of adipocytes differentiated from diabetic adipose-derived stem cells and prevents excessive lipogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported the anticancer property of squalene [26] . Ganbold et al [27] reported a new amphiphilic squalene derivative improves metabolism of adipocytes differentiated from diabetic adipose-derived stem cells and prevents excessive lipogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Adipogenesis, a developmental process to form fat tissue as energy storage tissue in which excess energy is stored in the form of lipids in adipocytes, is controlled by a complex cascade of adipocyte-specific transcription factors such as peroxisome proliferator-activated receptor γ (Pparg), CCAAT/enhancer-binding protein α (Cebpa), perilipin 2 (Plin2), fatty acid synthase (Fasn) and sterol regulatory element binding transcription protein 1 (Srebp1) [ 27 , 28 ]. Furthermore, the specific regulation of cellular interactions in conjunction with many differentiation factors and extracellular matrix components are essential for the adipogenic differentiation process, such as signaling pathways, adhesion molecules and transcription factors [ 23 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, CpGs of MTOR were hypermethylated in the body region, which could involve a higher expression of this gene. PRKAA2 was associated with glucose levels after OGTT, and this gene seems to be related to insulin sensitivity [ 44 ] and some polymorphisms have been associated with T2DM [ 45 ]. Furthermore, PRKAA2 is closely related to MTOR regulation, i.e., downregulation of PRKAA2 induces MTOR expression and an increase in protein synthesis and insulin resistance in rats [ 46 ].…”
Section: Discussionmentioning
confidence: 99%